A sequential bioreactor adaption strategy enhanced the precipitation of metals from tailings' leachates. (15th August 2021) - Villa Gomez, D.K.; Serrano, A.; Peces, M.; Ryan, B.; Hofmann, H.; Southam, G.
Graphical abstract: Highlights: A bioreactor was operated for 172 days with different metal loads. Addition of tailings leachate increased the bioreactor efficiency up to 85% Metal removal reached values close to 100%, except for Mn, Ca and Mg. The inoculum shifted to a functional SRB community dominated by Desulfovibrionaceae. The addition of metals enhanced the activity of the methanogens in the bioreactor. Abstract: This study demonstrated the adaption of a sulfidic microbial community to mixed metal mine wastes, i.e., tailings leachate solutions, while maintaining bioreactor performance. This overall process occurred using a sulfate reducing bioreactor operated in continuous mode for 172 days with ethanol as electron donor and, at first, a synthetic mine solution and then, tailings leachate solutions. Remarkably, the addition of a succession of leachates increased the sulfate removal efficiency, which reached values around 84.7 ± 6.9% after the sulfate adaptation period. This increase was also in line with an increase in the soluble chemical oxygen demand removal efficiency and with a slight increase in the pH of the reactor. This high activity supported metal removal efficiencies close to 100% for most metals, except Mn, Ca and Mg whose precipitation was lower (80, 50 and 38%, respectively). The bacterial community in the bioreactor was initially diverse but evolved to be dominated by SRB, in particular Desulfovibrionaceae . Interestingly, the addition of the tailings leachates enriched for the presence of methanogens in the bioreactor, consistent with the consumption of the accumulated acetate.